Curcurmin Micronization from Temulawak (Curcuma Xanthorrhiza) Extract Using Supercritical Co2 as Anti-Solvent - Sugeng Winardi; Trifena Widyasari Christy; Shinta Showiantari; Sarah Duta Lestari; Siti Machmudah; Kusdianto Kusdianto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
The aim of this study is to compose curcumin microparticle from temulawak extract (curcuma xanthorrhiza) using SAS (Supercritical Anti-Solvent) method with supercritical CO2. Curcumin is made from temulawak extract that insoluble in water. One of method to increase solubility of curcumin in water is decrease particle size. SAS method is being chosen using supercritical CO2 as anti-solvent because temulawak is perfectly soluble in supercritical CO2. Micronization is performed inside precipitator equipped with filter at the bottom. Temperature is being operated in 35 and 40 oC, and in pressure 8 and 10 MPa. Flow rate ratio supercritical CO2 to solution is 15;0,25 and 15;0,30 mL/min. The results show significant effect of pressure and ratio flow rate Supercritical CO2 to solution on the morphology of micronized curcumin particles. The suitable conditions for curcumin micronization in this work were found to be at 8 MPa, 35 oC and flow rate ratio CO2 to solution is 15;0,25 mL/min.The Supercritical Anti-Solvent (SAS) method could be employed for the micronization curcumin particles. Moreover, the dissolution rate curcumin particles using SAS is higher than unprocessed curcumin particles.